Module-rating technology of teaching, as a basic condition of successful preparation of teacher in the individualized departmental teaching. - Aghyppo A.Y (Kharkov National Pedagogical University, 2010)
Notion of the module and rating is examined in the given article and characterized, in particular, a led principle of technology of the module teaching, and the scales of estimations for construction of rating of effectiveness of educational activity of students come into question. In addition, by the author is resulted the variant of module-rating technology, where connection of two technologies of teaching (module and rating) in single is - module-rating allows not only successfully to master educational material but also to conduct the objective control and estimation of knowledge's of students. It is single out conditions of successful individual teaching of students using module-rating technologies.